Stable water isotopes (δ^1?O, δ^1?O, δD) from deep ice at Prudhoe Dome, NW Greenland - Vasileios Gkinis; Jeppe Brøndum Bach; Caleb K Walcott-George; Allie Balter-Kennedy; Nicolás E Young; Tanner W Kuhl; Elliot Moravec; Jason P Briner; Joerg Schaefer (PANGAEA, 2025)
We present here a water isotope record (δ^1?O, δ^1?O, δD) from Prudhoe Dome, NW Greenland. The record spans the depth range 76.7–509.4?m (bedrock depth) and has a youngest age of 7.1?±?1.1?ka at the bottom, estimated by single-grain luminescence dating on potassium feldspar grains. Water isotope measurements were performed on ice chips collected after each 3?m drill run. We used cavity ring-down spectroscopy (Picarro L-2140i) with a high-throughput vaporizer (Picarro A0212). Isotope ratios are reported in per mil ( extperthousand) relative to the Vienna Standard Mean Ocean Water and Standard Light Antarctic Precipitation (VSMOW–SLAP) international scale. Measurement precision was determined to be ±0.025 extperthousand for δ^1?O, ±0.021 extperthousand for δ^1?O, and ±0.23 extperthousand for δD. The measurement and validation protocols are described in Gkinis (2021).